Application of Webgis Distribution Location Puskemas in Labuhanbatu District - Muhammad Wahyu Tambunan; Ibnu Rasyid Munthe; Gomal Juni Yanris (Institute of Computer Science (IOCS), 2021)
The community finding a place for health services is difficult, so a research was conducted in the form of creating a puskesmas map application to assess the puskesmas in Labuhanbatu Regency. Since this research has gone well, Labuhan Regency people can know the information and help them find health centers faster after this webgis is installed. Study of the life cycle of system development using SDLC (Systems Development Life Cycle) using UML to design spatial information systems to help solve problems. This will help the public to locate the nearest health center.